Printed circuit board design for reduction of common-mode radiation - Aung Myo Oo (2008)
Recently, radiated electromagnetic interference (EMI) has become a major design issue for high speed circuit designers, and it is likely to become even more severe in the future. With increasing operational speeds of circuits, electronic products may not pass the EMI regulatory standards such as FCC, CISPR, etc. Therefore, it is critical to design an electronic system with Electromagnetic Compatibility (EMC) consideration.